2019
DOI: 10.1007/s11606-019-04884-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Resident Assessment in Graduate Medical Education: Review of the Literature

Abstract: BACKGROUND: Competency-based medical education relies on meaningful resident assessment. Implicit gender bias represents a potential threat to the integrity of resident assessment. We sought to examine the available evidence of the potential for and impact of gender bias in resident assessment in graduate medical education. METHODS: A systematic literature review was performed to evaluate the presence and influence of gender bias on resident assessment. We searched Medline and Embase databases to capture relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 30 publications
1
114
0
Order By: Relevance
“…Differences in the assessment of men and women have been documented within undergraduate and graduate medical education. [18][19][20][21][22][23][24][25][26][27][28] Most notably and recently, Dayal et al 20 studied the effect of gender on milestone assessments in EM residency training programs. Dayal and colleagues found that at the beginning of training, milestone assessments tend to be similar between men and women, with women achieving higher mean scores in many categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the assessment of men and women have been documented within undergraduate and graduate medical education. [18][19][20][21][22][23][24][25][26][27][28] Most notably and recently, Dayal et al 20 studied the effect of gender on milestone assessments in EM residency training programs. Dayal and colleagues found that at the beginning of training, milestone assessments tend to be similar between men and women, with women achieving higher mean scores in many categories.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from undergraduate and graduate medical education have demonstrated gender differences associated with several assessment methods. [18][19][20][21][22][23][24][25][26][27][28] For example, men in EM residencies achieve higher milestone assessments than women at graduation. 20 With the revised format of the SLOE 2 and the tendency for more SLOEs to be completed by groups of EM residency and clerkship leaders, 9,15 rather than individual faculty, we sought to determine if there is any difference in the SLOE global assessment of female versus male applicants.…”
mentioning
confidence: 99%
“…3,4 This gender disparity persists later in residency training and as attending physicians. [5][6][7] Women in medicine do not receive the same recognition as their male colleagues in terms of leadership and salary. 8-10 These patterns might be reflecting the gendered pathways female medical students are encouraged to pursue, which tend to be lower paid and underappreciated, as are most professions and careers dominated by women.…”
mentioning
confidence: 99%
“…Klein et al 6 performed a systematic review of the literature from 1998 to 2018 to examine the presence and influence of gender bias on resident assessment. Five of the nine studies uncovered evidence of gender bias, with women receiving lower ratings in domains of performance and differences in qualitative comments.…”
mentioning
confidence: 99%